2008
DOI: 10.3390/medicina44070068
|View full text |Cite
|
Sign up to set email alerts
|

Are religious delusions related to religiosity in schizophrenia?

Abstract: This article attempts to explore the phenomenology of religious delusions in patients suffering from schizophrenia and to determine parallels between personal religiosity and content of religious delusions. We have studied the content of delusions in patients with schizophrenia looking for religious themes using Fragebogen fur psychotische Symptome (FPS) – a semistructured questionnaire developed by the Cultural Psychiatry International research group in Vienna. A total of 295 patients suffering from schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
0
24
0
3
Order By: Relevance
“…Religious delusions were particularly frequent in Catholic individuals with schizophrenia. In another study by the same authors, the sociocultural factors of gender, marital status, and education level revealed differences in religious based delusions [69]. In this study, it was found that men were more likely to describe themselves as Gods while women identified as Saints [69].…”
Section: Religious Delusions and Schizophreniamentioning
confidence: 49%
See 2 more Smart Citations
“…Religious delusions were particularly frequent in Catholic individuals with schizophrenia. In another study by the same authors, the sociocultural factors of gender, marital status, and education level revealed differences in religious based delusions [69]. In this study, it was found that men were more likely to describe themselves as Gods while women identified as Saints [69].…”
Section: Religious Delusions and Schizophreniamentioning
confidence: 49%
“…In another study by the same authors, the sociocultural factors of gender, marital status, and education level revealed differences in religious based delusions [69]. In this study, it was found that men were more likely to describe themselves as Gods while women identified as Saints [69]. In this study, married individuals had fewer apocalyptic delusions, and lower levels of education were more predictive of religious based delusions [69].…”
Section: Religious Delusions and Schizophreniamentioning
confidence: 52%
See 1 more Smart Citation
“…Les délires apocalyptiques et de fin de monde ont aussi été analysés dans le cadre du diagnostic des troubles mentaux et ont été problématisés dès les débuts de la psychiatrie moderne (De Martis, 1965 ;Rudaleviciene et al, 2008a), en particulier chez les patients souffrant de formes de schizophrénie aux causes encore mal élucidées. Ceux-ci ne semblent plus en contact avec leur environnement et présentent des dysfonctionnements cognitifs (hallucinations visuelles, mais surtout auditives), comportementaux et sociaux souvent associés à des sentiments de persécution exprimés dans des délires.…”
Section: Les Délires Apocalyptiques Et De Fin De Monde Parmi Les Patiunclassified
“…Cette convergence entre les deux groupes à cet égard se vérifie de nouveau dans une enquête plus récente (Tateyama et al, 1993). Ces délires peuvent s'accompagner d'idées grandioses et d'identification à des figures religieuses (réincarnation d'archanges, Christ/Messie et à Dieu) (Vardy et Kaplan, 2008 ;Silva et al, 1997), avec des différences de genre : les hommes se déclarant plus significativement être une divinité que les femmes, qui se prenaient plutôt pour des saintes (Rudaleviciene et al, 2008b). Selon des études de cas psychiatriques, des patients souffrant de délires apocalyptiques prétendent ainsi être l'incarnation de l'Antéchrist, comme le rapporte le récit d'un homme de 32 ans, de confession protestante.…”
Section: Les Délires Apocalyptiques Et De Fin De Monde Parmi Les Patiunclassified